Against the grain: The dialectical conception of culture in the theses of Walter Benjamin (1940) - Löwy, Michael (Lutas Sociais, 2011)
Based on an original and inventive reading ofWalter Benjamin’s seventh thesis on the concept ofhistory (1940), this article discusses the possibilityand the necessity of a dialectical conceptionof culture. Guided by concrete examples fromLatin American history, the author demonstratesthe timeliness of the necessity – proclaimedby Benjamin – of “writing history against thegrain,” conceiving it from the point of view of thevanquished, in opposition to the official history of“progress,” whose identification with the dominantclasses hides the utopian ideas inscribed in thestruggles of the oppressed, past and the present.